Robust H∞ Filtering and Deconvolution for Continuous Time Delay Systems Based on Game-Theoretic Approach - You, Fuqiang; Li, Hui; Wang, Fuli; Guan, Shouping (Asian journal of control, 2016)
Many dynamical systems involve not only process and measurement noise signals but also parameter uncertainty and unknown input signals. This paper aims to estimate the state and unknown input for linear continuous time‐varying systems subject to time delay in state, norm‐bounded parameter uncertainty, and a known input. Such a problem is reformulated into a two‐player differential game whose saddle point solution gives rise to one sufficient solvable condition for the estimation problem. The possible optimal estimators are obtained by solving the two coupled Riccati differential equations. We demonstrate, through two examples, how the proposed estimator is valid for estimating state and unknown input.